Host-Guest Complexations of Amine Boranes and Isoelectronic/Isostructural Quaternary Alkylammonium Cations by Cucurbit[7]uril in Aqueous Solution - Mona A. Gamal-Eldin; Donal H. Macartney (Heteroatom Chemistry)
The host-guest complexation of six amine boranes (R3NBH3) by the macrocyclic host molecule cucurbit[7]uril (CB[7]) in aqueous solution has been investigated using 1H and 11B NMR spectroscopy. The limiting complexation-induced 1H and 11B chemical shift changes indicate that the amine boranes are included in the hydrophobic cavity of the host molecule. The host-guest stability constants for neutral  R3NBH3∙CB[7]  complexes (in the range of 105-107M-1) have been determined by 1H NMR competition experiments and are compared with the corresponding values for the isoelectronic/isostructural  R3NCH3∙CB[7] + complexes. Ammonia borane (H3NBH3) does not form a host-guest complex with CB[7]. The trends in the host-guest stability constant with the guest molar volume are examined, and the stability is ascribed to the hydrophobic effect (packing coefficient) and quadrupole-dipole interactions.